KERAGAAN SISTEM AGRIBISNIS KAKAO (Theobroma Cacao) DI KABUPATEN BOLAANG MONGONDOW UTARA - Vicky ., Suoth; Agnes Estephina Loho; Eyverson ., Ruauw (Sam Ratulangi University, 2019)
The purpose of this study was to examine the performance of the cocoa agribusiness system in the North Bolaang Mongondow Regency. This research was carried out for 6 months from January to June 2018. Theresearch location was chosen purposively where Kaidipang District and Bolaang Itang District were the centers of cocoa production in North Sulawesi. The samples taken were all members of the two Farmer Groups selected from the two selected sub-districts namely the Tolerant Farmers Group and the Advanced Advanced Farmers Group. Primary data was obtained through direct interviews with 16 respondents from the Joint Advanced Farmers Group and 19 respondents from the Tolerant Farmers Group so that the total respondents were 35 people. Interviews are conducted based on a list of questions that have been prepared previously. Direct observations are also made regarding plant cultivation and maintenance activities. Secondary data was obtained from the relevant agencies regarding the production data and the size area of cocoa land obtained from the Plantation Office and the Central Statistics Agency. Analysis of the data used is descriptive analysis. The results showed that upstream agribusiness agri-business activities in the form of use of sprayers, scissors, knives, lawn mowers, fertilizers and pesticides. The activities of the agriproduction subsystem in the form of cultivation techniques include the use of production facilities and cultivation technologies such as continuous entries. On subsystem activity. downstream agri industry, farmers are still in a simple stage where fruit processing still uses sun-drying techniques. While in the farmer'sagricultural system activities, it sells cocoa to village traders and district traders. The supporting subsystem has not yet worked on all subsystems, as in the subsystem of the management role of the supporting institutions it has not played a role in causing farmers to only be price recipients. The cocoa agribusiness system has occured but has not worked efficiently.*eprm*